Examining corporate social responsibility activities of BIST 100 companies following the 2023 Turkiye-Syria earthquakes - Durmus, Gokmen; Mutlu, Mustafa Doruk; Turkmenoglu, Mehmet Ali (Emerald Group Publishing Ltd, 2025)
PurposeThis study investigates the corporate social responsibility (CSR) activities of BIST-100 companies in response to the Turkiye-Syria earthquakes of 2023. It aims to classify and analyze the CSR efforts made by these companies through their social media (X) posts, contributing to an understanding of how firms engage in disaster relief.Design/methodology/approachA qualitative content analysis was performed on X posts by BIST-100 companies (the 100 highest stocks listed in the Istanbul Stock Market), covering the period between February 6 and June 18, 2023. The posts were categorized based on their scope, speed and type of support using Forcadell and Aracil's CSR framework. The companies' actions were classified into symbolic, reactive, passive and active CSR responses.FindingsThe analysis revealed that the majority of BIST-100 companies adopted a symbolic CSR strategy, offering limited support over a short period. However, a minority of companies demonstrated active or reactive strategies, providing diverse and sustained aid. Companies addressing a wider range of stakeholders were more likely to use an active CSR strategy.Originality/valueThis study expands on existing CSR frameworks by applying them to the context of a natural disaster, specifically the Turkiye-Syria earthquakes. It offers insights into how major Turkish companies respond to crises and the effectiveness of their CSR activities while contributing to the literature by introducing a local disaster-based assessment model.
Keywords: Corporate Social Responsibility; Philanthropic Responses; Earthquakes; Social Media; Turkiye; Qualitative Analysis